STUDI TENTANG PELAKSANAAN KEGIATAN BELAJAR SABLON DI PKBM CAHAYA ILMU KELURAHAN TUAH KARYA KECAMATAN TAMPAN KOTA PEKANBARU - Hannissha Novia; Titi Maemunaty; Widiastuti ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Non-formal education is divided into several institutes, there fare PKBM Cahaya Ilmu as one of the non-formal educational institutes make a learning programs for society that is screen priting training program, the purpose of this training is to let the public who follow this training to able to create their own business. The purpose of this research is to know the implementation of screen printing learning activities in PKBM Cahaya Ilmu. This research was done using qualitative methods from phenomenology type, these methods are descriptive which aims to describe the exact reality ageinst a phenomenon that is happening. There are three informant in this research , main informant, observer informant, and control informant. The research result in the implementation of screen printing learning activities in PKBM Cahaya Ilmu is very good because this activities capable of passing all their citizen who take part in this activities an they all can absorb the lesson that been provided well as prevision capabilities for their life in the corporate world.Keyword: The implementation of screen printing learning activities